Investigation of solution chemistry effects on sorption behavior of Cu(II) on ZSM-5 zeolite - Zhang, Lipeng (Water environment research : a research publication of the Water Environment Federation, 2011)
The sorption of Cu(II) from an aqueous solution using ZSM-5 zeolite was investigated by batch technique under ambient conditions. Sorption was investigated as a function of pH, ionic strength, foreign ions, humic substances, and temperature. The results indicate that the sorption of Cu(II) on ZSM-5 zeolite is strongly dependent on pH. Sorption is dependent on ionic strength at low pH, but independent of ionic strength at high pH values. The presence of humic/fluvic acid (HA/FA) enhances the sorption of Cu(II) on ZSM-5 zeolite at low pH values, and reduces Cu(II) sorption at high pH values. Sorption isotherms were well simulated by the Langmuir model. Thermodynamic parameters (i.e., deltaH0, deltaS0 and deltaG0) for the sorption of Cu(II) were determined from temperature-dependent sorption isotherms at 293.15, 313.15, and 333.15 K, respectively. Results indicate that the sorption process of Cu(II) on ZSM-5 zeolite is spontaneous and endothermic